Social determinants of health and well-being among municipal school children in Mumbai - Kazi, Yasmeen K.; Shenoy, Anita G.; Velhal, Gajanan D.; Mate, Suresh D.; Suryawanshi, Sudam R. (International Journal Of Community Medicine And Public Health, 2017)
Background: HBSC seeks to identify and explore the extent of the inequalities related to socioeconomic status (SES), age and gender among the younger age group, and highlight the need for preventive action. Hence, this study was carried out, to find out the social context as a determinant of their health and well-being. The objectives of the study were to study the socio-demographic characteristics of the students; to find the social determinants and its association with their perceived health outcomes. Methods: The study was carried out among 426 Municipal school students in Mumbai. They were enquired about their socio demographic characteristics, their personal habits and behaviour, relationship with their parents, siblings and friends, performance in school, academic pressures, and also about any health related complaints if they had. Results: The study shows less communication of students with their parents, more so with their fathers’. Students were seen to have more friends and would also spend more time with them, especially boys. Academic achievement was better among girls and those from less affluent families and it also showed a dip in the higher age groups. Regular consumption of breakfast, fruits, vegetables was seen less among girls and older students. Boys and those from less affluent families were seen to be more involved in high risk behaviour. Conclusions: All the factors mentioned in the study are shown to have adverse effects on the perceived health outcome of the students. These social factors need to be addressed to improve the health and well-being of the younger generations.